Testicular histomorphology, sperm and testicular morphometric evaluation of glyphosate exposed rabbit bucks treated with hydro-alcoholic leaf extract of Newbouldia laevis - Anietie Archibong Ansa; Chioma Vivian Odegbunam; Ogechi Grace John; Favour Ifeoma Obidike (Acta Scientiarum. Animal Sciences, 2024)
This study investigated the effect of glyphosate exposure on some male reproductive parameters and the potential protective effects of Newbouldia laevis leaf (NBL) extract. The 36 rabbits used for the study were randomized into four treatment groups (control, glyphosate-only, glyphosate + NBL 100 mg and glyphosate + NBL 200 mg) in a completely randomized design. From the results, glyphosate was found to significantly impair all measured semen parameters. Testicular morphometric analysis revealed a significant (p < 0.05) decrease in some testicular parameters due to glyphosate exposure. Histological examination of testes in the glyphosate-only group revealed severe disruptions in testicular architecture, likely contributing to the observed decrease in semen quality. Conversely, NBL treatment led to significant enhancement in spermatogenic activity, resulting in higher sperm count, motility, volume, libido, live sperm, and improved sperm morphology when compared to the herbicide-exposed group. NBL-treated groups exhibited significant (p < 0.05) increase in testicular circumference, width, and epididymal length. NBL extract also restored testicular architecture and ameliorated herbicide-induced histological changes. Therefore, the potential protective effects of Newbouldia laevis leaf extract on herbicide-induced reproductive dysfunction could pave the way for novel natural interventions to counteract the negative consequences of herbicide exposure.